Evaluation of unilateral condyle head fracture on panoramic and CBCT imaging: a case report - Putri, Meiryndra Syaira; Sam, Belly; Epsilawati, Lusi (Ikatan Radiologi Kedokteran Gigi Indonesia, 2025)
Objectives: This case report aimed to describe the radiographic characteristics of the fracture of the condyle’s head and its impact on surrounding tissues in a young adult patient using panoramic and CBCT radiographs. Case Report: A 19-year-old female patient presented to the Dental Radiology Unit of Dental Hospital Universitas Padjadjaran with a panoramic and periapical referral letter, diagnosed clinically with a dental fracture of the upper left central incisor, and planning to have orthodontic treatment. The patient had a history of a motorcycle accident in early January 2024 and was hit on the left side of her face. Extraoral examination revealed an asymmetrical facial appearance with mandible deviation, mouth opening limitation, and crepitation on palpation test. Intraoral examination showed a traumatic ulcer in the upper left lip region (tooth 22) and a dental fracture on tooth 21. Oral hygiene was in good condition. The first panoramic radiograph (January 19th, 2024) showed a fracture on the right condyle’s head. It referred to taking the CBCT examination (May 28th, 2024) to know the exact position and the destruction of the condyle’s head. The CBCT examination showed a radiolucent line crossing horizontally on the left condyle’s head; the joint space was larger than on the other side. Conclusion: Based on the CBCT results in terms of location and radiographic feature, this radiolucent line led to a suspect radiodiagnosis of unilateral fracture on the left condyle’s head that causes pain and limited mouth opening. Keywords: CBCT, condyle’s head, fracture, panoramic, temporomandibular joint